ESOMEPRAZOL IN TREATMENT OF GASTROESOPHAGIAL REFLUX DISEASE IN CHILDREN AND ADOLESCENTS - R.T. Saygitov ("Paediatrician" Publishers LLC, 2008)
The results of trials of activity of esomeprazol in children with gastroesophagial reflux disease (gerd) are presented in this article. It was marked that esomeprazol (Nexium) can be used in children of 1-11 years (10 or 20 mg daily) and 12-17 years (20 or 40 mg daily) with gerd according to modern recommendations. The information about acid suppressor activity of esomeprazol in children with gerd younger then 2 years old (0,25-1 mg/kg daily) was published. Clinical activity of esomeprazol was confirmed in a number of randomized and open labeled, developed in different countries, including Russia. At the same time main results of activity of this medication were obtained in investigations of adult patients with gerd. This fact indicates necessity of provision of wide ranging trials, which could make complete assessment of advantages and safety profile of esomeprazol. Key words: children, adolescents, gastroesophagial reflux disease, esomeprazol, treatment.